ANTI-GAD AND C-PEPTIDE IN EARLY-ONSET NON-OVERWEIGHT PATIENTS WITH TYPE 2 DIABETES: IMPLICATIONS FOR LADA SCREENING (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the prevalence of anti-GAD positivity, fasting C-peptide levels, and associated factors in order to suggest screening for latent autoimmune diabetes in adults (LADA).Methods: A cross-sectional descriptive study was conducted on 76 patients with diabetes mellitus. Serum anti-GAD antibodies, fasting C-peptide, blood glucose, HbA1c, and lipid profiles were measured. Comparisons between groups were performed using Fisher’s exact test and the Mann–Whitney U test. Multivariable linear regression analysis was used to identify factors associated with fasting C-peptide levels.Results: The prevalence of anti-GAD positivity was 5.3%, while 13.2% of patients had low fasting C-peptide levels. Patients with positive anti-GAD tended to have greater β-cell dysfunction compared to those with negative anti-GAD. The low C-peptide group had significantly higher fasting blood glucose and HbA1c levels than the normal/high C-peptide group (p < 0.05). The multivariable regression model was statistically significant (p = 0.007), showing that glucose and HDL-c were independently and inversely associated with fasting C-peptide levels.Conclusion: β-cell dysfunction was closely associated with poor glycemic control in patients with early-onset diabetes. Autoimmune features may be present in a small subgroup of patients. Measurement of fasting C-peptide and anti-GAD may be useful for patient stratification and treatment orientation.
Keywords: Latent autoimmune diabetes in adults (LADA), Anti-glutamic acid decarboxylase antibody (Anti-GAD), C-peptide, β-cell dysfunction.